2023
DOI: 10.1038/s41467-023-35990-7
|View full text |Cite
|
Sign up to set email alerts
|

An integrated Mg battery-powered iontophoresis patch for efficient and controllable transdermal drug delivery

Abstract: Wearable transdermal iontophoresis eliminating the need for external power sources offers advantages for patient-comfort when deploying epidermal diseases treatments. However, current self-powered iontophoresis based on energy harvesters is limited to support efficient therapeutic administration over the long-term operation, owing to the low and inconsistent energy supply. Here we propose a simplified wearable iontophoresis patch with a built-in Mg battery for efficient and controllable transdermal delivery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…A recently reported breakthrough idea is integrated battery-powered controllable transdermal DDSs . These platforms can provide advantages such as self-powered therapeutic administration induced by an internal energy source for long-term operations .…”
Section: Future Directions For Peptide Delivery Formulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently reported breakthrough idea is integrated battery-powered controllable transdermal DDSs . These platforms can provide advantages such as self-powered therapeutic administration induced by an internal energy source for long-term operations .…”
Section: Future Directions For Peptide Delivery Formulationsmentioning
confidence: 99%
“…230 These platforms can provide advantages such as self-powered therapeutic administration induced by an internal energy source for long-term operations. 230 They can also potentially be integrated with long-acting peptide delivery formulations (e.g., peptide-loaded/conjugated micro/nanoparticles, hydrogels, and scaffolds) to lead to further clinical benefits, resulting in better patient comfort. For example, in Zhou et al's study, a wearable built-in Mg battery-powered iontophoresis patch was reported for efficient and controlled transdermal drug delivery for noninvasive chronic disease treatment.…”
Section: Future Directions For Peptide Delivery Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, tuning the electrical properties of materials is extremely desired not only for electronics but also for other fields like electrochemistry and biomedicine where the occurring phenomena can ultimately be reduced to electron/ion conductivity and surface charge accumulation . That is, the design of electrodes for sensing, , the optimization of energy storage devices, the synthesis of actuators and the study of biological processes, such as cell growth, antibiotic activity or drug release, among many others. Nevertheless, the design of novel molecular engineered or metamaterials is moving at a slower pace compared to other fields such as electromagnetism, , as the characteristic wavelength of electrical-related phenomena requires accurate control on the structure and periodicity of materials down to the atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…1). For example, viologen-containing polymers such as side-chain, [41][42][43][44][45] mainchain, 46,47 dendrimer, [48][49][50] network, 51,52 and composite 53 have been reported to exhibit low electrochromic voltage and/or good film-forming performance. [54][55][56][57][58] Therefore, viologen and viologen-containing polymers could be used to prepare interesting electrochromic devices (ECDs).…”
Section: Introductionmentioning
confidence: 99%